FT-IR and FT-Raman spectroscopic study of surface species of 2-aminopyridine adsorbed by sepiolite from Anatolia - Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Springer US, 1999)
The adsorption of 2-aminopyridine by Anatolian sepiolite was investigated by Fourier-transform infrared and Fourier-transform Raman spectroscopy. The spectroscopic results indicate that 2-aminopyridine molecules adsorbed on sepiolite are coordinated to Lewis acidic centers or surface hydroxyls by H-bonding interaction through the pyridine ring nitrogen lone pairs. No physical sorbed species has been detected. Monocationic surface species has also not been detected under the conditions applied. It must be noted that the adsoiption of aminopyridine affected the hydroxyl group vibrations of sepiolite.
Keywords: Raman Spectrum; Sepiolite; Ring Nitrogen; Nitrogen Lone Pair; Zeolitic Water